Measuring Effort–Reward Imbalance in School Settings: A Novel Approach and Its Association With Self-Rated Health - Li, Jian (Japan Epidemiological Association, 2010)
BACKGROUND: We attempted to apply the model of effort–reward imbalance (ERI) to school settings in order to measure students’ psychosocial stress and analyze its association with self-rated health in adolescents. METHODS: A cross-sectional survey was conducted in Kunming, China among 1004 Chinese students (468 boys and 536 girls) in grades 7 through 12, using a 19-item effort–reward imbalance questionnaire. RESULTS: Satisfactory internal consistencies for the scales for effort and reward were obtained; the value for the scale for overcommitment was acceptable. Factor analysis replicated the theoretical structure of the ERI construct in this sample of Chinese students. All 3 scales were associated with an elevated odds ratio for diminished self-rated health, and the effect was strongest for the effort–reward ratio, as predicted by the theory. Sex and grade differences were also observed. CONCLUSIONS: The ERI questionnaire is a valid instrument for identifying sources of stressful experience, in terms of effort–reward imbalance, among adolescents in school settings.